Propensities for the formation of individual disulfide bonds in hen lysozyme and the size and stability of disulfide-associated submolecular structures - Tachibana, Hideki (FEBS letters, 2000)
Hen lysozyme single-disulfide variants were constructed to characterize the structures associated with the formation of individual native disulfide bonds. Circular dichroism spectra and the effective concentration of protein thiol groups showed that the propensity for structure formation was relatively high for Cys-6–Cys-127 and Cys-30–Cys-115 disulfides. The urea concentration dependence of individual effective concentrations showed that the apparent sizes of the structures were 14–50% of the whole molecule. The intrinsic stability of each submolecular structure in a reduced form of protein, obtained by subtracting the entropic contribution of cross-linking, was highest for Cys-64–Cys-80 and lowest for Cys-76–Cys-94 disulfide bonds.